E-SKILLS IP – MASTERING THE 21ST CENTURY SKILLS - Loureiro, Ana (2015)
In this paper we will present the results of a case study carried out with attendees of an Erasmus Intensive Programme (e-skills IP - Competences for Collaboration and Knowledge Sharing in Digital Society), which has promoted the development of 21st century skills among participants. The 21st century skills are a set of abilities that students need to develop in order to succeed in the information age. The Intensive Programme took place during 2014 spring in Timisoara, Romania involving the participation of teachers (with skills in the areas of ICT, digital literacy, non-formal education and intervention, design & illustration and teacher education) and students (of teacher training, social education and intercultural relations and migration fields) from four different countries. The classes covered different tools and six tutors were involved. At the end, attendees were: able to master the different tools & applications; capable to use and select the most adequate web 2.0 tools & applications according with a specific situation; able to create and manage their PLE/N; able to share and work collaboratively in a synchronous and asynchronous way; able to communicate an idea and to interact with peers from different countries. The working methodology was hands on workshop based and a package of a two and a half weeks of sessions covering a variety of web 2.0 tools was prepared and delivered to the participants. The e-skills IP had a positive impact in the participants since they saw their 21st century skills enhanced along with foreign language skills improvement. They had the opportunity to learn about different cultures through the nation nights activities and to discover a bit more about cultural aspects of the host region/country through the social events. A website was built in order to aggregate all the contents and results of the IP. The IP gave an intense overview about the different tools that are available in the web 2.0 and that can be very useful for teaching/learning activities. Learning, literacy and life skills are key competences in this information age, with an impact not only in our daily lives but also in our professional and academic careers.